2021
DOI: 10.3892/mmr.2021.11977
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin‑3‑O‑β‑glucoside protects against pulmonary artery hypertension induced by monocrotaline via the TGF‑β1/p38 MAPK/CREB signaling pathway

Abstract: Pulmonary artery hypertension (PAH) is a disease with high morbidity and mortality. Cyanidin-3-O-β-glucoside (Cy-3-g), a classical anthocyanin, has a variety of biological effects. The present study evaluated whether Cy-3-g attenuated PAH, and explored the potential mechanism of action. Rats were injected with monocrotaline (MCT; 60 mg per kg of body weight) and then treated with Cy-3-g (200 or 400 mg per kg of body weight) for 4 weeks. Protein expression was determined in vitro in transforming growth factor-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In this regard, anthocyanins, natural pigments belonging to the flavonoid family, are widely distributed in the human diet, such as in beans, fruits, vegetables, and red wine [ 8 ]. It is well-accepted that these natural compounds present in fruits and plant-derived-foods are relevant because of their potential health-promoting effects, as suggested by the available experimental and epidemiological evidence [ 9 , 10 , 11 ]. For this reason, interest in the biochemistry and biological effects of anthocyanins has increased substantially during the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, anthocyanins, natural pigments belonging to the flavonoid family, are widely distributed in the human diet, such as in beans, fruits, vegetables, and red wine [ 8 ]. It is well-accepted that these natural compounds present in fruits and plant-derived-foods are relevant because of their potential health-promoting effects, as suggested by the available experimental and epidemiological evidence [ 9 , 10 , 11 ]. For this reason, interest in the biochemistry and biological effects of anthocyanins has increased substantially during the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…The SCFA butyrate can promote B10 cell generation by activating the p38 MAPK pathway [ 39 ]. The p38 MAPK pathway is activated in pulmonary hypertension [ 40 , 41 , 42 ]. We found an increased abundance of Ruminococcaceae in the HySu-induced group at week 4.…”
Section: Discussionmentioning
confidence: 99%
“…While blackberry consumption itself was unable to decrease p-SAPK/JNK, other studies utilizing individual polyphenols, such as C3G, have demonstrated their ability to reduce other MAPKs, p38 specifically, in a model of pulmonary HTN. 50 Unexpectedly, blackberry consumption had no effect on antioxidant enzymes in the lung. However, given the minimal appearance of oxidative stress and blackberries ability to mitigate ROS production through decreased NOX4, antioxidant responses may have been unneeded.…”
Section: Papermentioning
confidence: 95%